Gut microbiome sheds light on the development and treatment of abdominal aortic aneurysm - Ling, Xuebin; Jie, Wei; Qin, Xue; Zhang, Shuya; Shi, Kaijia; Li, Tianfa; Guo, Junli (Frontiers in Cardiovascular Medicine, 2022)
Abdominal aortic aneurysm (AAA) is an inflammatory vascular disease with high disability and mortality. Its susceptible risk factors include old age, being male, smoking, hypertension, and aortic atherosclerosis. With the improvement of screening techniques, AAA incidence and number of deaths caused by aneurysm rupture increase annually, attracting much clinical attention. Due to the lack of non-invasive treatment, early detection and development of novel treatment of AAA is an urgent clinical concern. The pathophysiology and progression of AAA are characterized by inflammatory destruction. The gut microbiota is an “invisible organ” that directly or indirectly affects the vascular wall inflammatory cell infiltration manifested with enhanced arterial wall gut microbiota and metabolites, which plays an important role in the formation and progression of AAA. As such, the gut microbiome may become an important risk factor for AAA. This review summarizes the direct and indirect effects of the gut microbiome on the pathogenesis of AAA and highlights the gut microbiome-mediated inflammatory responses and discoveries of relevant therapeutic targets that may help manage the development and rupture of AAA.